IMPORTANCE OF CAPITAL MARKET PARTICIPANTS IN THE TRANSITION TO A GREEN ECONOMY - Omonov Sardor Ulmasovich (Scholar Express Journals, 2025)
This article studies importance of capital market participants in the transition to a green economy, the importance of green financial instruments and their types. The role of green investors in the capital market, the functions of capital market participants in the transition to a green economy, and the share of green bonds in the international green bond market by type are analyzed. Based on the analysis, relevant conclusions are given.
Keywords: financing; economy; green economy